2017
DOI: 10.5860/crl.v78i1.16568
|View full text |Cite
|
Sign up to set email alerts
|

Investigating Textbook Reserves: A Case Study of Two Models for Reserves Collections

Abstract: This article examines the behaviors and preferences of medical and nursing students in relation to their required textbooks and library reserves. The findings are based on an April 2015 survey at the University of Illinois-Chicago satellite Library of the Health Sciences in Urbana, where the library provides access to textbooks through traditional “closed” reserves in addition to an “open” reserves collection. Results indicate several barriers to usability regarding traditional reserves services and suggest th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2017
2017
2019
2019

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 7 publications
0
3
0
Order By: Relevance
“…Two articles offer an excellent overview of current course reserves-related literature, including Stephanie Pitts-Noggle and Ryan Rafferty's 2017 work on piloting an open reserves collection, and a 2009 piece on the UCLA Library's strategic partnership with their campus bookstore by Anne Christie et al 2,3 Both of these articles point to a study by the Government Accountability Office in 2005 that found that textbook prices since 1978 had increased at twice the rate of inflation and suggest that many academic libraries responded to this finding by offering expanded course reserves services in an effort to reduce some of the textbook-cost burden on students. Pitts-Noggle and Rafferty show that although significant work has been done legislatively and in the academy to bring down prices, textbook costs have remained the same.…”
Section: Reading the Literaturementioning
confidence: 99%
“…Two articles offer an excellent overview of current course reserves-related literature, including Stephanie Pitts-Noggle and Ryan Rafferty's 2017 work on piloting an open reserves collection, and a 2009 piece on the UCLA Library's strategic partnership with their campus bookstore by Anne Christie et al 2,3 Both of these articles point to a study by the Government Accountability Office in 2005 that found that textbook prices since 1978 had increased at twice the rate of inflation and suggest that many academic libraries responded to this finding by offering expanded course reserves services in an effort to reduce some of the textbook-cost burden on students. Pitts-Noggle and Rafferty show that although significant work has been done legislatively and in the academy to bring down prices, textbook costs have remained the same.…”
Section: Reading the Literaturementioning
confidence: 99%
“…The dominant trend of assessment in libraries has influenced how librarians advocate, particularly with a focus on outcomes that clearly enumerate to stakeholders how students benefit from having access to librarians. [1][2][3][4] Administering pre-and-post tests showing how students who received instruction performed and linking information literacy participation to graded course assignments are examples of quantifiable forms of student advocacy. Test results, the number of classes taught, and student attendance represent tangible data.…”
Section: Advocacymentioning
confidence: 99%
“…As Stephanie PittsNoggle and Ryan Rafferty found in their 2015 survey of students at the University of Illinois-Chicago's satellite Library of the Health Sciences in Urbana, differences in usage and rates of user satisfaction indicate that open reserve collections better suit patrons' needs and is the more successful model for a reserve textbook collection. 6 The Alverno Open Reserve Textbook Collection (AORTC) was modeled after the Library of the Health Sciences-Urbana's (LHSU) open reserve textbook collection but adapted to meet the needs of the Alverno student body. When LHSU students were specifically surveyed about the open reserves collection, the most agreed with statement (81%) was that students liked being able to use materials without checking them out.…”
Section: An Open Reserve Collectionmentioning
confidence: 99%